Donor-specific antibodies require preactivated immune system to harm renal transplant - Süsal, Caner; Döhler, Bernd; Ruhenstroth, Andrea; Morath, Christian; Scherer, Sabine; Tran, Thuong Hien; Gombos, Petra; Schemmer, Peter; Zeier, Martin; Opelz, Gerhard (EBioMedicine, 2016)
Background - It is an unresolved issue why some kidney transplant recipients with pretransplant donor-specific HLA antibodies (DSA) show a high transplant failure rate, whereas in other patients DSA do not harm the graft. We investigated whether help from preactivated T-cells might be necessary for DSA to exert a deleterious effect. - Methods - The impact of pretransplant DSA and immune activation marker soluble CD30 (sCD30) on 3-year graft survival was analyzed in 385 presensitized kidney transplant recipients. - Findings - A deleterious influence of pretransplant DSA on graft survival was evident only in patients who were positive for the immune activation marker sCD30. In the absence of sCD30 positivity, 3-year graft survival was virtually identical in patients with or without DSA (83.1±3.9% and 84.3±2.8%, P=0.81). A strikingly lower 3-year graft survival rate of 62.1±6.4% was observed in patients who were both sCD30 and DSA positive (HR 2.92, P<0.001). Even in the presence of strong DSA with ≥5000 MFI, the 3-year graft survival rate was high if the recipients were sCD30 negative. - Interpretation - Pretransplant DSA have a significantly deleterious impact on graft survival only in the presence of high pretransplant levels of the activation marker sCD30.